2017
DOI: 10.1111/dom.12973
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease (NAFLD) prevalence and its metabolic associations in patients with type 1 diabetes and type 2 diabetes

Abstract: We investigated non-alcoholic fatty liver disease (NAFLD) prevalence and its metabolic associations in patients with type 1 diabetes (T1D), and in insulin-naïve and insulin-treated patients with type 2 diabetes (T2D). Baseline data from patients who had liver fat content (LFC) evaluated by magnetic resonance imaging in four phase 3 studies of basal insulin peglispro (BIL) were analysed. Associations of NAFLD with clinical characteristics, glycaemic control and diabetes therapy were evaluated. The prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
131
5
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 20 publications
12
131
5
14
Order By: Relevance
“…Hepatic steatosis is known to strongly correlate with high glucose levels . However, until now, only a single study has investigated the association between HGI and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatic steatosis is known to strongly correlate with high glucose levels . However, until now, only a single study has investigated the association between HGI and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…It can progress to steatohepatitis, cirrhosis and even hepatocellular carcinoma, which is associated with high mortality rates . Furthermore, NAFLD has a strong association with metabolic parameters, including HbA1c . In Korea, the prevalence of NAFLD is estimated to be approximately 20‐30% and is rapidly increasing as a result of an increasingly Westernized lifestyle.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent European Association for the Study of the Liver guidelines recommend screening for fatty liver in patients at risk, including those who meet the criteria for metabolic syndrome (MetS), by obtaining their alanine aminotransferase (ALT) level and a liver ultrasound . Several studies have shown the high burden of NAFLD and advanced fibrosis in patients with type 2 diabetes (T2D), making them a high target for screening . However, multiple issues surround the proposition to screen for NAFLD in high‐risk groups, including the lack of cost‐effectiveness studies.…”
Section: Challenge #1: Most Patients With Nash‐associated Advanced Fimentioning
confidence: 99%
“…Liver fat content was assessed at baseline and after insulin treatment in these diabetes cohorts [12]. In correlations of baseline LFC with baseline values of lipoproteins and other soluble biomarkers, we found that large VLDL, VLDL size, Apo C3, and small LDL had the strongest and most consistent positive correlations with LFC, with r values of 0.216‒0.460 across the diabetes cohorts.…”
Section: Discussionmentioning
confidence: 93%
“…Changes in particle size of LDL, HDL, and VLDL were also compared. The objectives and results of the LFC study have been reported elsewhere [11, 12]. …”
Section: Introductionmentioning
confidence: 99%